2007
DOI: 10.1002/dvg.20296
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a conditional knockout allele for mammalian Spen protein Mint/SHARP

Abstract: The Spen protein family is found in worms, flies, and mammals, and is implicated in diverse biological processes from embryogenesis to aging. Spen proteins have three N-terminal RNA recognition motifs and a C-terminal SPOC domain. The mammalian Spen proteins Mint and its human ortholog SHARP interact with the Notch-signaling mediator RBP-J as well as Msx2 and several unliganded nuclear hormone receptors, and impart transcription-repressing activity to these molecules by recruiting corepressors through the SPOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Overexpression of GIT2 resulted in the significant dose-dependent elevation of the expression of multiple DNA repair proteins, e.g., HMGN1 (36) and RFC1 (41), as well as proteins involved in nuclear responses to cytotoxic DNA damage (NOP2 [42]) or involved in aging/neurodevelopment (SPEN [43]) (see Fig. S3a and b in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of GIT2 resulted in the significant dose-dependent elevation of the expression of multiple DNA repair proteins, e.g., HMGN1 (36) and RFC1 (41), as well as proteins involved in nuclear responses to cytotoxic DNA damage (NOP2 [42]) or involved in aging/neurodevelopment (SPEN [43]) (see Fig. S3a and b in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, mutant mouse models lacking the components of Notch pathways (Notch2, ref. (5). These data clearly indicate that Notch2-mediated signals favor MZB fate at the branching point for the FOB versus MZB fate decision and regulate the balance between FOB and MZB development.…”
Section: Discussionmentioning
confidence: 70%
“…During B cell maturation, signals driven by cell-surface receptors and downstream transcription factors must be regulated in a coordinated fashion to maintain mature B cell homeostasis. In particular, both B cell antigen receptor (BCR) and BAFF, the B cell-activating factor belonging to the TNF family, relay crucial signals for mature B cell development and survival, while the Notch pathway regulates MZB cell development (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice deficient for the murine SHARP homologue MINT die during late embryogenesis (21). Studies using fetal liver transfer and a conditional knockout approach have shown a SHARP deficiency to cause hematopoietic defects in marginal zone B-cell development and T-cell development (21,39,45).…”
mentioning
confidence: 99%